2019
DOI: 10.3897/mycokeys.61.38175
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and secondary chemistry in species recognition of Parmelia omphalodes group – evidence from molecular data with notes on the ecological niche modelling and genetic variability of photobionts

Abstract: To evaluate the importance of morphological and chemical characters used in the recognition of species within the Parmelia omphalodes group, we performed phylogenetic, morphological and chemical analyses of 335 specimens, of which 34 were used for molecular analyses. Phylogenetic analyses, based on ITS rDNA sequences, show that P. pinnatifida is distinct from P. omphalodes and the most important difference between those species is the development of pseudocyphellae. In P. pinnatifida, they are mostly marginal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 95 publications
3
16
0
3
Order By: Relevance
“…The three Pseudephebe species show no substantial differentiation with regard to photobiont use, based on haplotype distribution, Fst values and the specialization parameter d' for both ITS and RPL10A. This scenario aligns with previous reports of closely related lichenized fungi sharing the photobiont pool partially or completely (Beck et al 1998;Hestmark et al 2016;Onuţ-Brännström et al 2017;Singh et al 2017;Dal Grande et al 2018;Ossowska et al 2019) and opposes to cases in which ecological speciation drove photobiont differentiation, as in the Lichina-Rivularia symbiosis (Ortiz-Álvarez et al 2015). This is reflected in the most prevalent haplotypes 1 (ITS) and 2 (RPL10A) that are shared by the three mycobiont species across continents and regions spanning different climatic conditions.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The three Pseudephebe species show no substantial differentiation with regard to photobiont use, based on haplotype distribution, Fst values and the specialization parameter d' for both ITS and RPL10A. This scenario aligns with previous reports of closely related lichenized fungi sharing the photobiont pool partially or completely (Beck et al 1998;Hestmark et al 2016;Onuţ-Brännström et al 2017;Singh et al 2017;Dal Grande et al 2018;Ossowska et al 2019) and opposes to cases in which ecological speciation drove photobiont differentiation, as in the Lichina-Rivularia symbiosis (Ortiz-Álvarez et al 2015). This is reflected in the most prevalent haplotypes 1 (ITS) and 2 (RPL10A) that are shared by the three mycobiont species across continents and regions spanning different climatic conditions.…”
Section: Discussionsupporting
confidence: 87%
“…In coherence with previous ecological and evolutionary findings on parmeliod lichens (Opanowicz and Grube 2004;Ohmura et al 2006;Fernández-Mendoza et al 2011;Leavitt et al 2015;Ossowska et al 2019), all species of the genus Pseudephebe are found in association with microalgae of the genus Trebouxia throughout their entire geographic range. More specifically, the dominant photobiont is Trebouxia S02, which belongs into the Trebouxia clade S (Leavitt et al 2015;Muggia et al 2020) as identified using phylogenetic analyses.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…От близких видов P. pinnatifida и P. discordans отличается наличием лишайниковых кислот и морфологическими особенностями псевдоцифелл. Виды P. omphalodes и P. pinnatifida содержат атранорин, лобариевую и салациновую кислоты, а таллом P. discordans -протоцетраровую кислоту (Ossowska et al, 2019). Псевдоцифеллы P. pinnatifida маргинальные и ламинальные, а у видов P. omphalodes и P. discordans только маргинальные (Ossowska et al, 2019).…”
Section: P Ernstiaeunclassified
“…Этот эпилитный вид относится к лишайникам, чьи ареалы охватывают горные и холодные регионы планеты (Ossowska et al, 2019). На территории Беларуси к таким видам относятся следующие эпилиты: Montanelia sorediata (Ach.)…”
Section: P Ernstiaeunclassified